2005
DOI: 10.1111/j.1365-2052.2005.01318.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence for hybridization of species in the genusGallusexcept forGallus varius

Abstract: A phylogenetic tree for fowl including chicken in the genus Gallus and based on mitochondrial D-loop analysis further supports the hypothesis developed from morphology and progeny production that red junglefowl (RJF) is the direct ancestor of the chicken. The phylogenetic positions of the chicken and the other fowl species in the genus Gallus are of great importance when considering maintenance and improvement of chicken breeds through introgression of genetic variation from wild-type genomes. However, because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
128
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(133 citation statements)
references
References 16 publications
2
128
1
2
Order By: Relevance
“…The previous reference sequence NC_001323 (Desjardins and Morais, 1990) likely had sequencing errors, including excessive indels, and it was abandoned (Figure 2). Variants in the mtDNA sequences were scored relative to the new reference sequence NC_007235 (Nishibori et al, 2005). The classification of the variants of each chicken mtDNA genome was performed with mtDNAGeneSyn v.1.0 (Pereira et al, 2009).…”
Section: Sequence Analysismentioning
confidence: 99%
“…The previous reference sequence NC_001323 (Desjardins and Morais, 1990) likely had sequencing errors, including excessive indels, and it was abandoned (Figure 2). Variants in the mtDNA sequences were scored relative to the new reference sequence NC_007235 (Nishibori et al, 2005). The classification of the variants of each chicken mtDNA genome was performed with mtDNAGeneSyn v.1.0 (Pereira et al, 2009).…”
Section: Sequence Analysismentioning
confidence: 99%
“…In the current work, we compared our population‐level results with other studies (e.g., Akaboot et al., 2012; Berthouly et al., 2010; Granevitze et al., 2007; Liu et al., 2006; Miao et al., 2013; Nishibori et al., 2005; Okumura et al., 2006; Peterson & Brisbin, 1998) that also addressed genetic exchange between feral or free‐ranging domestic chickens and so‐called wild Red Junglefowl. Advantageously, these studies used Red Junglefowl also obtained from South and Southeast Asia.…”
Section: Discussionmentioning
confidence: 99%
“…Red Junglefowl still commonly exist in their native habitats (Brickle et al., 2008; Brisbin, 1995) and are clearly distinguishable from domestic chickens (Johnsgard, 1999). Although genetic contributions from multiple Junglefowl species may have played a role in the domestication process (Eriksson et al., 2008; Nishibori, Shimogiri, Hayashi, & Yasue, 2005), archeological and genetic evidence (Fumihito et al., 1994, 1996; Gongora et al., 2008; Storey et al., 2012; Thomson et al., 2014) indicate that Red Junglefowl from Southeast Asia was the primary progenitor of all domestic breeds of modern chickens. In a previous study, we identified substantial haplotype variation in the major histocompatibility complex (MHC) B‐locus of wild Red Junglefowl (Fulton et al., 2016; Nguyen‐Phuc, Fulton, & Berres, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Archaeological research has identified centres of chicken domestication in India and China; both within the natural range of wild Junglefowl (Crawford, 1990). Chickens were likely domesticated from wild Red Junglefowl, though some have suggested possible genetic contributions from other Junglefowl species (Eriksson et al, 2008;Nishibori et al, 2005). Darwin (1896) was the first to propose that all domestic fowls descended directly from one common ancestor; the Gallus Bankiva, or wild Junglefowl breed that originated in Eastern and Southern Asia.…”
Section: Introductionmentioning
confidence: 99%